Analisis Pemahaman Konsep Mahasiswa Pendidikan Fisika Universitas Sriwijaya pada Materi Gravitasi Newton dengan Menggunakan NGCI Dan CRI Termodifikasi - Rahayu, Anita Yuza; Syuhendri, Syuhendri; Sriyanti, Ida (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
This research aims to analyze about conceptual understanding and misconceptions on material Newtonian Gravity of students physics education Sriwijaya University. Data collected by  using test NGCI (Newtonian Gravity Concept Inventory), CRI (Certainty of Response Index), and Interview to discribed types of conceptual understanding students’. Analysis methods  data used Descriptive qualitative technique. Based on the analysis CRI, this research find 28,51 % student understand the concept, 4,68 % understand the concept but not sure , 27,9% misconception, and 25,62 % not understand the concept. The most misconception occurs in sub concept the relations of mass to the gravitational force that is 49,65 %. This research can be used for basic research increase student conceptual understanding